Teacher Problem Analysis in the Development of Biology Learning Tools Integrated by Reading Questionning and Answering (RQA) Learning Model in Senior Highschool - Winarno Winarno; Makrina Tindangen; Evie Palenewen (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2018)
This study adressed three aspects: (1) how Senior Highshool Biology teachers perceive about learning tools (2) how the skills of Senior Highshool Biology teachers in managing learning tools (3) what are problems obtained by teachers according to planning and implementation of learning tools with the integration of Reading, Qusetioning and Answering (RQA). This study is the prerequisite study to analyse the needs for the development of learning tools integrated by Reading, Questioning and Answering (RQA) in Senior Highschool. Method used in this study is qualitative descriptive. The conculion obtained from this study includes: (1) the lack of expertise about learning tools in Senior Highschool Biology teachers, (2) the lack of ability in them to manage learning tools, (3) problems obtained in them related to the planning and implementation of the learning tools integrated by Reading, Qusetioning and Answering (RQA) learning model.